2013
DOI: 10.3109/14397595.2013.843760
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of adalimumab in Japanese rheumatoid arthritis patients: Postmarketing surveillance report of 7740 patients

Abstract: Adalimumab, especially with concomitant use of MTX, provided significant improvement in disease activity, without any unexpected ADRs in Japanese RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
61
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 37 publications
17
61
2
Order By: Relevance
“…Recently, the CONCERTO trial demonstrated that 10 mg/week of MTX is a possible dosage for use in combination with TNF inhibitors (30). Moreover, the unique situation in Japan has provided interesting data showing that concomitant MTX of 7-8 mg/week works additively with TNF inhibitors (31)(32)(33). These studies support our finding that concomitant use of even a low dose of MTX may be useful for reducing the incidence of large joint replacement in patients treated with TNF inhibitors.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, the CONCERTO trial demonstrated that 10 mg/week of MTX is a possible dosage for use in combination with TNF inhibitors (30). Moreover, the unique situation in Japan has provided interesting data showing that concomitant MTX of 7-8 mg/week works additively with TNF inhibitors (31)(32)(33). These studies support our finding that concomitant use of even a low dose of MTX may be useful for reducing the incidence of large joint replacement in patients treated with TNF inhibitors.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, other biologics with different mechanisms of action are reported to be more effective in treating RA when administered with concomitant MTX [19,[28][29][30][31][32][33][34]. Further studies are needed to determine the mechanisms that account for this difference.…”
Section: Discussionmentioning
confidence: 64%
“…18 Up to now, post-marketing surveillance of biological agents in Japan has not detected any cases of de novo hepatitis due to HBV reactivation. [19][20][21] These studies were of sufficient size to detect uncommon adverse events, although the observation period was only 6 months. A nationwide survey of fulminant hepatitis and late-onset hepatic failure was conducted in Japan from 2004 to 2009.…”
Section: Discussionmentioning
confidence: 99%